Imunização infantil na atenção primária em saúde: hesitação vacinal entre pais e perspectiva de profissionais - Benício, Janaína Alves (2023)
Vaccines were developed with the aim of preventing diseases and saving lives, the National Immunization Program has identified a drop in vaccine coverage, with a resurgence of preventable diseases. Vaccine Hesitation is among these factors and has worried managers and researchers due to its increase. The objective of the study was to analyze Vaccine Hesitation among parents and the perspective of health professionals about child immunization in Primary Health Care, in the city of São Bentinho-PB. An observational, cross-sectional and descriptive study was carried out, with a quantitative approach. The sample consisted of 200 parents of children, registered in the Family Health Strategy of that municipality, and 23 professionals from the health teams. The data obtained were processed in the SPSS program, with descriptive analysis, and the chi-square test was applied, considering significant p˂0.05 values. As for the results regarding the parents of children, it was observed that the majority were female (n=190, 95%), with the mother (n=182, 91%) being the main guardian. The prevalence of Vaccination Hesitation was 0.5% (1/200). Parents believed that it would be better for their children to receive fewer vaccine doses at a time (44%) and that children received more vaccine doses than they needed (13%). Although 40.5% of parents reported delaying (28%) or failing to vaccinate their children (12.5%), and that 30.5% were concerned about possible vaccine adverse events, most thought it was important to follow the vaccination schedule. vaccination (99.5%), as well as declared their intention to continue vaccinating their children in the future (99.5%). Most Family Health Strategy professionals (65.2%) did not have a course on vaccination. More than half (52.2%) knew how to identify difficulties that could lead parents to Vaccination Hesitation. The results indicate a low prevalence of Vaccination Hesitation; suggest parental confidence in the vaccination process and professionals, although they claim to be afraid of severe vaccine reactions; parents have a high level of intention to vaccinate children, but a low level of adherence is observed; Updating information from professionals and passing it on to parents is necessary and can contribute positively to the process of more effective vaccination.